To An approach to understanding communicative competences - Ardila Higuera, Jenny Andrea; Muñoz Tibocha, Andrea Ximena; Jiménez Vega, Laura Marcela (Rastros Rostros, 2023)
The main purpose of the article is to reflect on the importance of communicative competence that arises from the heart of linguistics and that addresses different perspectives from the command of the language in different contexts. In the first place, the definition of competence is presented so that the student identifies the capacities in terms of academic and labor competence, on which the optimization of the domains of knowledge and attitudes necessary to relate in the workplace is based. Communicative competence raises the use of language in various components and approaches such as linguistic, sociolinguistic, psycholinguistic, and pragmatic, which conceive a communicative performance based on the social environment that implies identifying the processes of the sender - receiver that allows understanding the function of communication. Appropriate in learning situations that require degrees of autonomy to actively assume participation with other people. Communication skills are considered as key elements necessary for the development of communicative competence such as active listening, assertive communication, and development in contexts such as family, work, and virtual environments. Thus, the study of communicative competence implies knowing how to communicate, knowing how to apply knowledge and that knowledge that allows us to differentiate a holistic vision from a rigid one, in which a training process is necessary to obtain mastery of the discursive scheme to act in the social scene
Keywords: Competence; ability; capacity; performance